Pengaruh Penggunaan Bioaktivator tehadap Produksi Usahatani Padi - Rahayu Relawati; Istis Baroh (AGRIMOR, 2023)
Bioactivators or biological fertilizers are materials containing microorganisms used by rice farmers with the aim of increasing rice production so as to create increased food security. This study aims to analyze the production, income of rice farming and the effect of bioactivators and other production inputs on rice farming production. The research was conducted at the Margo Santoso Farmer's Group, Ngajum Village, Malang Regency. Simple random sampling was used as a determinant of sampling. The population of farmers is known to be 102 people and a sample of 50 respondents was taken using the Slovin formula calculation. Data analysis using Cobb Douglass production function. The results showed that the average rice production and income of rice farming using bioactivators was 9.385 kg/ha with an income of Rp. 30.886.260 /Ha while those who do not use bioactivator 7.817 kg/Ha with an income of Rp. 23.329.566 /Ha. The results showed that simultaneously the variables of seed, fertilizer, pesticide, labor, and bioactivator had an effect on the rice production variable, while partially the pesticide, labor, and bioactivator variables had a significant effect on rice production, but the seed and fertilizer variables had no significant effect on the rice production. rice production. Strategies that can be used to increase rice farming production by adding a bioactivator by 1% will increase rice production by 19,9%, adding a workforce of 1% will increase production by 17,7% and adding pesticides by 1% will increase production 8,7%. However, adding 1% of seeds can only increase production by 5% and adding 1% fertilizer only increases production by 8,4%.